ELECTRICAL CONDUCTIVITY, THERMOPOWER AND 57FE MöSSBAUER SPECTROSCOPY OF AEGIRINE (NAFESI2OO6) - Schmidbauer E.; Kunzmann Th. (My University, 2004)
DC and AC electrical conductivities were measured on samples of two different crystals of the mineral aegirine (NaFeSi2O6) parallel (∥) and perpendicular (⊥) to the [001] direction of the clinopyroxene structure between ∼200 and ∼600 K. Impedance spectroscopy was applied (20 Hz-1 MHz and the bulk DC conductivity σDC was determined by extrapolating AC data to zero frequency. In both directions, the log σDC - 1/T curves bend slightly. In the high- and low-temperature limits, differential activation energies were derived for measurements ∥ [001] of EA ∼0.45 and ∼0.35 eV, respectively, and the numbers ⊥ [001] are very similar. The value of σDC ∥ [001] with σDC(300 K) ∼2.0 × 10-6 Ω-1cm-1 is by a factor of 2-10 above that measured ⊥ [001], depending on temperature, which means anisotropic charge transport. Below ∼350 K, the AC conductivity σ′(ω) (ω/2π = frequency) is enhanced relative to σDC for both directions with an increasing difference for rising frequencies on lowering the temperature. An approximate power law for σ′(ω) is noted at higher frequencies and low temperatures with σ′(ω) ∝ ωs, which is frequently observed on amorphous and disordered semiconductors. Scaling of σ′(ω) data is possible with reference to σDC, which results in a quasi-universal curve for different temperatures. An attempt was made to discuss DC and AC results in the light of theoretical models of hopping charge transport and of a possible Fe2+ → Fe3+ electron hopping mechanism. The thermopower Θ (Seebeck effect) in the temperature range ~360 K < T < ∼770 K is negative in both directions. There is a linear Θ - 1/T relationship above ∼400 K with activation energy EΘ ∼0.030 eV ∥ [001] and 0.070 eV ⊥ [001]. 57Fe Mössbauer spectroscopy was applied to detect Fe2+ in addition to the dominating concentration of Fe3+.
Keywords: Electrical conductivity; Impedance spectroscopy; Thermopower; 57Fe Mössbauer spectroscopy; Aegirine